The trouble with goats and sheep [book club bag] : a novel - Cannon, Joanna (Psychiatrist) (Scribner, 2016)
Part coming-of-age story, part mystery, The Trouble with Goats and Sheep is a quirky and utterly charming debut about a community in need of absolution and two girls learning what it means to belong. England, 1976. Mrs. Creasy is missing and the Avenue is alive with whispers. The neighbors blame her sudden disappearance on the heat wave, but ten-year-olds Grace and Tilly aren<U+2019>t convinced. As the summer shimmers endlessly on, the girls decide to take matters into their own hands. Inspired by the local vicar, they go looking for God<U+2014>they believe that if they find Him they might also find Mrs. Creasy and bring her home. Spunky, spirited Grace and quiet, thoughtful Tilly go door to door in search of clues. The cul-de-sac starts to give up its secrets, and the amateur detectives uncover much more than ever imagined. As they try to make sense of what they<U+2019>ve seen and heard, a complicated history of deception begins to emerge. Everyone on the Avenue has something to hide, a reason for not fitting in. In the suffocating heat of the summer, the ability to guard these differences becomes impossible. Along with the parched lawns and the melting pavement, the lives of all the neighbors begin to unravel. What the girls don<U+2019>t realize is that the lies told to conceal what happened one fateful day about a decade ago are the same ones Mrs. Creasy was beginning to peel back just before she disappeared.